TRANS WANDERINGS:: PERIPATETIC CLINIC WITH ADOLESCENTS IN THE SUS (PRÁXIS EM SAÚDE, 2025)
The present study aims to analyze the implications of territory in psychotherapy with a focus on gender issues from a peripatetic clinic perspective. It is relevant due to the gap in the existing literature on gender and territory in the Unified Health System (SUS). Methodology: Two peripatetic clinic sessions linked to the Family Health Strategy (ESF) were conducted. Results: The creation of a stronger therapeutic bond and a broader understanding of the case by considering social, environmental, and psychological factors within the territory itself, transcending the inside-outside paradigm of traditional clinical psychotherapy. This allows for more personalized care, strengthening the user’s capacity for self-care. Conclusion: The peripatetic clinic serves as resistance to institutional constraints and violence. It is necessary that the SUS, in addition to being conceived as collective health, is experienced as such.
Keywords: Peripatetic Clinic; Gender; Territory; Unified Health System